Keanekaragaman Coccinellid Predator sebagai Musuh Alami Hama Kutu-Kutuan pada Ekosistem Pertanaman Cabai Merah di Kecamatan Merawang, Kabupaten Bangka: Diversity of Predatory Coccinellids as Natural Enemies Pest of Fleas in the Red Chili Plantation Ecosystem in Merawang District, Bangka Regency - Luffi Pratiwi; Anggraeni; Rion Apriyadi (Departemen Biologi, Institut Pertanian Bogor, 2023)
Coccinellid beetles (Coleoptera), most of which are predatory species on small, soft-bodied insects. Predatory Coccinellids are biological agents that functions as pest control in cultivated plants. The control of plant pests needs the availability of data on potential coccinellid predators. This reserach aims to study the diversity, richness, evenness and dominance of predatory coccinellid and to determine their relationship with environmental microclimate parameters. The research was carried out in the red chili plantation ecosystem at Merawang District, Bangka Regency. Three stations were used, i.e., station 1, 2, and 3 in Kimak, Jada Bahrin, and Balunijuk villages, respectively. Predatory coccinellid were collected by hand picking and by using a sweep net. Data on diversity analyzed using the Shannon-Wiener, Data on richness analyzed using the Margalef, Data on evenness analyzed using the Pielow evenness indices. dominance species was analyzed using the Simpson formula. The results showed that there were 7 species of predatory coccinellid, namely Coccinella tranversalis, Harmonia octomaulata, Menochilus sexmaculatus, Coelephora. macullata, C. bisellata, Verania lineate, and V. discolor with diversity at a moderate level (1,254), evenness at a low level (0.239) , the richness at a low level (1,628), and dominance of coccinellid at a low level (0.369).